Analysis Of Risk Management, Operational Efficiency, And Sharia Financial Inclusion In The Operational Performance Of Insurance Services At The Setia Budi Medan Branch Of Syariah Pawnshop - Tafana Ariani Harahap; Maidalena Maidalena; Tri Inda Fadhila Rahma (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze risk management, operational efficiency, and Islamic financial inclusion in supporting the operational performance of insurance services at Pegadaian Sharia Setia Budi Medan. The research used a descriptive qualitative approach involving 15 informants and analyzed using NVivo 14 through the stages of open coding, axial coding, and selective coding. The results of the study show that risk management is the most dominant theme in supporting the operational performance of insurance services. The application of risk identification, risk assessment, and determination of risk attitudes and solutions is able to maintain asset security and service quality. Operational efficiency is supported by administrative digitalization, non-cash transactions, and resource optimization, while Islamic financial inclusion is realized through the provision of accessible products, public education, and the use of digital technology. Overall, the operational performance of insurance services at Pegadaian Syariah Setia Budi Medan Branch is in good condition, supported by effective risk management, optimal operational efficiency, and wider Islamic financial inclusion.